The Effect of Return on Assets (ROA) and Return on Equity (ROE) on the Movement of Sharia Stock Prices of PT. Bank Syariah Indonesia Tbk for the Period 2021-2024 - Rahmat, Paisal; Nisa Brt, Ainun; Sari Siregar, Enni; Sanusi, Afriadi (Sharia Economic and Management Business Journal (SEMBJ), 2026)
The number of stock investors in 2024 reached 6.37 million stock investors out of a total of 14.84 million capital market investors. This share price is determined based on transactions that occur on the stock exchange market, namely in the form of investor demand and supply, so it is very important for investors to have the expertise to determine which company and when is the right time to buy shares. It can also be seen through how much the company is profitable, Return On Asset (ROA) and Return On Equity (ROE) are indicators that can measure the company’s ability to generate profits. This study aims to determine the effect of Return On Asset (ROA) and Return On Equity (ROE) on stock price movements at PT Bank Syariah Indonesia Tbk for the 2021-2024 period. By using Quantitative research methods. The test t results on the Return On Asset (ROA) variable Probability value <0.005, which is equal to 0.0144, Ha is accepted, meaning that Return On Asset (ROA) has an influence on the movement of the share price of PT Bank Syariah Indonesia Tbk, and Return On Equity (ROE) with a Probability value> 0.05, which is equal to 0.4803 Ha is rejected, meaning that Return On Equity (ROE) has no influence on stock price movements at PT Bank Syariah Indonesia Tbk. Meanwhile, the Return On Asset (ROA) and Return On Equity (ROE) variables simultaneously produce a Probability value <0.05, namely 0.0009, so Ha is accepted, meaning that there is a simultaneous influence between the Return On Asset (ROA) and Return On Equity (ROE) variables on the share price movement of PT Bank Syariah Indonesia Tbk for the 2021-2024 period